Ratios of double to single ionization of He and Ne by strong 400-nm laser pulses using the quantitative rescattering theory - Chen, Zhangjin; Li, Xiaojin; Zatsarinny, Oleg; Bartschat, Klaus; Lin, C. D. (My University, 2018)
We present numerical simulations of the ratio between double and single ionization of He and Ne by intense laser pulses at wavelengths of 390 and 400 nm, respectively. The yields of doubly charged ions due to nonsequential double ionization (NSDI) are obtained by employing the quantitative rescattering (QRS) model. In this model, the NSDI ionization probability is expressed as a product of the returning electron wave packet (RWP) and the total scattering cross sections for laser-free electron impact excitation and electron impact ionization of the parent ion. According to the QRS theory, the same RWP is also responsible for the emission of high-energy above-threshold ionization photoelectrons. To obtain absolute double-ionization yields, the RWP is generated by solving the time-dependent Schrödinger equation (TDSE) within a one-electron model. The same TDSE results can also be taken to obtain single-ionization yields. By using the TDSE results to calibrate single ionization and the RWP obtained from the strong-field approximation, we further simplify the calculation such that the nonuniform laser intensity distribution in the focused laser beam can be accounted for. In addition, laser-free electron impact excitation and ionization cross sections are calculated using the state-of-the-art many-electron R-matrix theory. The simulation results for double-to-single-ionization ratios are found to compare well with experimental data and support the validity of the nonsequential double-ionization mechanism for the covered intensity region.